2013
DOI: 10.1158/1078-0432.ccr-12-3705
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Regulation between Raf/MEK/ERK Signaling and Y-Box–Binding Protein-1 Promotes Prostate Cancer Progression

Abstract: Purpose: Y-box-binding protein-1 (YB-1) is known to conduct various functions related to cell proliferation, anti-apoptosis, epithelial-mesenchymal transition, and castration resistance in prostate cancer. However, it is still unknown how YB-1 affects cancer biology, especially its correlations with the mitogen-activated protein kinase (MAPK) signaling pathway. Therefore, we aimed to examine the interaction between YB-1 and the MAPK pathway in prostate cancer.Experimental Design: Quantitative real-time PCR, We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
66
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 57 publications
7
66
0
Order By: Relevance
“…Both p38 MAPK and MAPK1 has been shown to regulate E-cadherin-mediated phenotypic switching in prostate cancer [12]. ERK2 was shown as an independent prognostic marker for prostate cancer [13]. In fact, ERK2 along with the Y-box binding protein was shown to promote prostate cancer progression [13].…”
Section: Discussionmentioning
confidence: 99%
“…Both p38 MAPK and MAPK1 has been shown to regulate E-cadherin-mediated phenotypic switching in prostate cancer [12]. ERK2 was shown as an independent prognostic marker for prostate cancer [13]. In fact, ERK2 along with the Y-box binding protein was shown to promote prostate cancer progression [13].…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, research found that knockdown of YB-1 caused a 50% reduction in cell invasion, and further investigation suggested that YB-1 regulated EMT by mammalian target of rapamycin and mitogen-activated protein kinase signaling (9,27). In melanoma, the stimulating function of YB-1 in proliferation, invasion, apoptosis resistance and chemoresistance and the regulation of YB-1 in EMT-related signaling pathways have been widely proved (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have regarded YB-1 as an oncoprotein due to its involvement in uncontrolled proliferation (2), apoptosis resistance (3), sustained angiogenesis (4), invasion and metastasis (5). Furthermore, YB-1 has been associated with chemotherapeutic resistance (6) and high YB-1 expression is closely linked to the poor clinical outcome in various types of cancer, including gastric (7), ovarian (8) and prostate (9). Other studies have suggested that the carcinogenic effect of YB-1 may be associated with epithelial-to-mesenchymal transition (EMT) (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The ribosomal S6 kinase (RSK) 2 family comprises a group of ERK/MAPK effectors that regulate diverse cellular functions by phosphorylating nuclear and cytoplasmic targets. Hyperactive RSK signaling regulates cell division in several types of cancer, including breast, prostate, and lung (1)(2)(3).…”
mentioning
confidence: 99%
“…Hyperactive RSK signaling regulates cell division in several types of cancer, including breast, prostate, and lung (1)(2)(3). The RSK inhibitor SL-0101 arrests MCF-7 cells (a breast cancer cell line) in the G 1 phase, and thereby inhibits their proliferation (1).…”
mentioning
confidence: 99%